The image of Vlachs in the works by Jan Długosz - Obara-Pawłowska, Anna (Balcanica Posnaniensia. Acta et studia, 2018)
Starting from the 14th century the the common border between Poland and Wallachia had a twofold dimension. On the one hand, after the annexation of the Ruthenian lands by Casimir the Great, Poland was directly bordering on Moldova, inhabited by the Vlachs, which together with the nearby Wallachia was becoming the subject of increasingly active diplomatic interventions of the Kingdom of Poland. On the other hand, however, the mountainous regions of southern Poland were a place where the groups of Vlachs settled, intermingled and, and co-existed with the Polish and Ruthenian population. As can be guessed, these circumstances resulted in an increased interest in the Wallachian people and a search for the basic information about this ethnic group by the representatives of the Polish political and intellectual elites. The purpose of the paper is to describe the opinions on Vlachs which can be found in the works of Jan Długosz, one of the most prominent chroniclers of the 15th century. The paper presents the opinions of this historian on such issues as: the origin of the Wallachian population, the circumstances of their emergence in the Slavic lands, religious relations, activities and typical Wallachian professions, and finally, the qualities which distinguished this nation.